The root colonizing fungi of the terrestrial orchid Cypripedium irapeanum - Valdés, María; Bautista Guerrero, Héctor; Martínez, Laura; Víquez, Rafael (Lankesteriana: International Journal on Orchidology, 2011)
This study investigated the mycorrhizal status and the identification of the fungi colonizing the roots of the terrestrial orchid Cypripedium irapeanu by restriction fragment length polymorphisms and by rDNA internal transcribed spacer sequencing. The orchid is endemic of differents regions in Mexico, Guatemala and Honduras; usually at 1400-2250 m. It grows mainly in the remaining oak forests of the highlands and it is in the Mexican red list of plants in danger. The oak forests in Mexico are threatened constantly. The microscopic examination of stained root segments of the orchid revealed the presence of fungal structures of both orchidioid fungi (pelotons and coyled hyphae) and dark septate endophytes (DSE) (mielinized hyphae and microsclerotia). Analysis of ITS1-5.8-ITS2 region sequences suggested that mycorrhizal tissue was dominated by Tulasnaceae: Sistotrema sp., Rhizoctonia solani, and Epulorhiza sp. Among the DSE one isolate revealed 100% similarity to Phomopsis sp XJ-05, and another one 99% to the fungal endophyte MUT 885 which are both reported as dark septate endophytes. The putative dark septate endophyte Phomopsis sp XJ-05 was isolated not only from the roots but also from the germinated seeds of C. irapeanum.